Potensi Serapan Karbondioksida (CO2) pada Beberapa Jenis Tumbuhan Lantai Hutan Dari Suku Araceae Di Taman Nasional Gunung Halimun- Salak, Jawa Barat - Mansur, Muhammad (Perhimpunan Biologi Indonesia, 2012)
Potential Absorption of Carbon Dioxide (CO2) in Some Plant species on The Forest Floor From Family of Araceae in The Gunung Halimun-Salak National Park, West Java. Study of carbon dioxide (CO2) absorption in some plant species on the forest floor from Family of Araceae conducted in the Gunung Halimun-Salak National Park, Resort Cidahu, West Java, on September 2011. The survey was conducted to inventory the species of Araceae that exist atthe study site. Thirty samples of the five species of Araceae has been chosen as the target of photosynthesis measurement. Six individuals from each species were measured as replicates,in which young and old leaves were measured from each individual. The results show that five species of Araceae are found in forest floor, namely; Schismatoglottis calyptrata, Schismatoglottis rupestris, Alocasia longiloba, Arisaema filiforme and Colocasia esculenta.Colocasia esculenta has a higher CO2 absorption rate (14, 288 ?mol/m2/s) than Arisaema filiforme (8,614 ?mol/m2/s), Alocasia longiloba (7,599 ?mol/m2/s), Schismatoglottis rupestris(7,078 mol/m2/s) and Schismatoglottis calyptrata (5,260 ?mol/m2/s). In general, old leaves of all species have higher chlorophyll contain and CO2 absorption rate than young leaves. Theoptimum photosynthetic rate in Schismatoglottis calyptrata occurred at 10:00 am (8,457 ?mol/m2/s) and the lowest at 16:00 pm (4,262 ?mol/m2/s).Keywords: CO2 absorption, Araceae, Gunung Halimun-Salak National Park.